Pengaruh Kedisplinan Kerja, Komunikasi Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Dinas Peternakan dan Kesehatan Hewan Kabupaten Probolinggo - Agung Yatiningrum; Supriyono Supriyono; Mochammad Ruslan (Fakultas Ekonomi Universitas Panca Marga, 2016)
This research was conducted at the Office of Animal Husbandry and Healthy Board of Probolinggo Regency with research variables, namely Discipline (X1), Communication (X2), and Motivation on Employee Performance (Y). The population of this research is all employees of Animal Husbandry and Animal Husbandry Office as many as 90 people at once sampled. Data analysis method is qualitative and quantitative analysis using seven formulas that is validity test, reliability test, multiple linear regression analysis, t test, F test, classical assumption test, and regression hypothesis with SPSS 22 for windows software. Based on the test result 1) t test (Partial) is obtained the significant of discipline (X1) on employee performance with t value ≥ t table (8,389 ≥ 1,988) (sig. 0,000> 0,05), for communication test result (X2) Employee with the value of t table ≥ t table (2,481 ≥ 1,988) (sig. 0.015 ≤ 0,05), while for the result of motivation test (X 3) on employee performance with t value table ≥ t arithmetic (2,530 ≥ 1,988) (sig. 0.013 <0.05). For test results 2) F test knows whether Discipline (X1), Communication (X2) and Motivation (X3) influence simultaneously (F) on Employee Performance (Y). F count> F table (64,088> 2.71) (Sig.0,000 <0.05) then H0 is rejected and Ha accepted. Based on the analysis result of the variables affecting employee performance, it can be seen that the dominant influence the employee performance is the disciplinary variable (X1).